Monitoring of agricultural drought using remote sensing data in the Sebou watershed, Morocco - El-Bouhali Abdelaziz; El Ouazani Ech-Chahdi Khadija; Amyay Mhamed (E3S Web of Conferences)
Drought is a climatic phenomenon that can adversely affect the environment and human activities. Currently, agricultural drought has become a concern in countries where agriculture largely depends on rainfall and is highly vulnerable to climatic variability. The study of drought requires the availability of hydroclimatic and remote sensing data. Based on these data, researchers have proposed several indices (SPI, SPEI, PDSI, VCI, VHI, etc.) that allow the monitoring of the spatiotemporal evolution of drought. This study focuses on remote sensing data to illustrate agricultural drought in the Sebou watershed from 2010 to 2023. We used the NDVI derived from MODIS (Moderate Resolution Imaging Spectroradiometer) satellite images to calculate the Vegetation Condition Index (VCI) during the crop growth season. The analysis of the VCI over 14 years shows that the Sebou watershed has undergone droughts of varying severity, with a notable increase in drought events from 2016 to 2023. In 2016, approximately 50% of the basin experienced extreme agricultural drought. Thus, we found that the VCI is a valuable indicator that reflects the vegetation's response to the rainfall deficit recorded in recent years.